Distance Learning Planning in Hindu Religious Education - Ni Putu Sri Pinatih; Santang (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
Planning is something that must be prepared before the main thing is carried out. Planning is needed to assist in realizing the learning objectives that have been previously set. Careful planning will be able to determine the outcome of learning activities carried out by a teacher or educator. Learning planning is the design of learning activities which can be in the form of a syllabus, learning implementation plan (RPP), and SAP. These three things are the development of the curriculum. Learning planning during the COVID-19 pandemic, namely learning activities carried out remotely or often referred to as distance learning. Teachers and students are not in the same place. To prepare for distance learning there are three main tasks in designing and implementing distance learning, where these three things must also be applied in planning Hindu religious education. The three things are 1) What (Content); 2. Who (Learning Profile, Current Conditions, and Needs); and 3. How (Design and implementation of learning).